Formation of international law and its relationship to domestic law - کول, مارف عمر (Sulaimani Journal for Humanities, 2001)
In this research we dealt with the subject of relation between the general int. law and the interior law, and to specify the correlation between the two laws. In the introduction of the research we confirmed on the necessity of knowledge of essence of the Int. law and its origins source for this purpose we divided this research into 4 section: The first section: the meaning of int. law. The second section: the origins of the Int.law. The third section: The emergence of the int. law. The fourth section: Some aspects of correlation between general int. law and state interior law. In the 1st section we have clarified the concept of the int. law. According to the different trends , then we came to a conclusion that its better to use int.law as a term instead of people or nation law since the other take part in the forming the int. law. In the 2nd section, we divided the Int.law origins into main origins and auxiliary origins. The main origins consists of customs general law principles and treaties we dealt with customs at the first becomes its existence priority treaty. While we clarified auxiliary origins pursuits to the paragraph (38) of the charter of the Int. court of justice. In the 3rd section , we talked about the emergence and formation of the Int.law from the 15th and 16th century also we have discussed the factors that helped in forming and developing the Int.law. those factors are in the scientific renaissance , the formation of National state, the emergence of geographical and marine sciences , the decreasing the ottoman courts authority towards the Europeans , West Falia conference, the American revolution 1775-1785 and French revolution 1789-1795, and then we reffered to the effects of the Int.events and establishing the Nation League and United Nation Organization. In last section , we discussed the theory of two laws, duality and the theory of law Unity concerning the relationship between the general Int. law and state interior law, and through the analysis the these two theories we confirmed that they are not considered as one law and can't be separated totally. But there is a clear relation between them. The Int.events confirmed the superiority of general Int.law on the interior law. Then we mentioned the states obligation , it's the international law rules, and in case of violating these obligations there will be an Int. responsibility of the Iraqi government as a result of it. Violating to the Int.law rule about the harsh treatment of the Kurdish people, and on the basis of Int. documents we conclude the kind of the Iraqi violation for its Int. obligations. In conclusion , we confirmed that the Int.law play, a prominent role in the state relation with the important issues of the human societies. And the research clarified the origins ay Int.law and it's relation with the emergence and development of Int.law then the sovergeinty of int.law had specified the state obligation regarding the nature of the interior law and its relation with the protection of human rights. And on the basis of all this we attached the research as number of formal documents for the Institution of Iraq Government. In order to appear the reality of violations of the Int. obligations. These documents has its implications that contradict with the collection of documents and the major rules of the Int. law concerning human rights.